Flexible Product Drying System Design and Application - Aküner, C.; Tuncay, M. T. (Elektronika ir Elektrotechnika, 2010)
Drying is removing the water in it with the various methods which cause quick spoil of the product. Increasing durability of the product by drying process, product quality influence such as appearance, color, taste, perfume, etc., and people's sense of appeal to the properties as possible protection, reduced energy consumption issues not overlooked. As a result of a high-quality drying process increases strength, reduces the volume and mass of the product. Control system of the rotary drum dryer has been developed which is previously designed and manufactured by the support of TUBITAK. Under Development National Instruments Company has produced the USB 6008 module LABVIEW program by using the operator intervention to ensure which were aimed clearly different variations of products in the drying process. In this study in the different profiles a wide range of products, with maximum quality and commercially low cost dryers, has been developed. Developed dryer is able to provide proper drying on each type of the product. By making appropriate changes on the operator panel of developed system can be performed drying for different products.